2012
DOI: 10.1097/ccm.0b013e3182377906
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of type III Pseudomonas aeruginosa bacteremia*

Abstract: Background Pseudomonas aeruginosa bacteremia is a serious and life-threatening infection associated with high mortality. Among the multitude of virulence determinants possessed by P. aeruginosa, the type III secretion system (TTSS) has been implicated with more acute and invasive infection in respiratory diseases. However, the relationship between TTSS and clinical outcomes in P. aeruginosa bacteremia has not been investigated. Objectives To determine the association between the TTSS virulence factor in P. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 31 publications
2
89
5
Order By: Relevance
“…Although this relationship was not assessed in our study, the exoS gene was found in all clinical isolates whilst the presence of the exoT and exoY genes varied, and unlike other studies (El-Solh et al, 2012;Wareham & Curtis, 2007), the presence of the exoU gene occurred at low frequency in our study (9.4 %).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Although this relationship was not assessed in our study, the exoS gene was found in all clinical isolates whilst the presence of the exoT and exoY genes varied, and unlike other studies (El-Solh et al, 2012;Wareham & Curtis, 2007), the presence of the exoU gene occurred at low frequency in our study (9.4 %).…”
Section: Discussioncontrasting
confidence: 47%
“…Indirect evidence from epidemiological studies suggests that fluoroquinolone resistance and expression of TTSS virulence are independently associated with poor outcomes resulting from MDR P. aeruginosa infections (Bleves et al, 2010;El-Solh et al, 2012;Roy-Burman et al, 2001;WongBeringer et al, 2008). Although this relationship was not assessed in our study, the exoS gene was found in all clinical isolates whilst the presence of the exoT and exoY genes varied, and unlike other studies (El-Solh et al, 2012;Wareham & Curtis, 2007), the presence of the exoU gene occurred at low frequency in our study (9.4 %).…”
Section: Discussionmentioning
confidence: 99%
“…One of the virulence mechanisms possessed by P. aeruginosa is known as TTSS, which is a syringe-like structure that allows the introduction of toxins (e.g., ExoS and ExoU) into target cell cytoplasm [26]. A substantial association between TTSS-associated virulence and poor clinical outcome for P. aeruginosa-infected patients has been reported [27], with higher incidence of massive tissue destruction and spread of blood infection and increased mortality, which was found to be higher with genotypes expressing various exotoxins rather than those with no toxin-expression [28,29]. For that reason, it was important to evaluate the association of the TTSS genotype related to surgical site infection.…”
Section: Discussionmentioning
confidence: 99%
“…T3SS also enhances infection severity in several animal models: acute pneumonia [19,21,52], keratitis [52], bacteremia [22], peritonitis [53], burn infections [20] and gut-derived sepsis in neutropenia [54]. Moreover, T3SS in vitro detection was correlated with increased morbi-mortality and relapse in human P. aeruginosa ventilator-associated pneumonia and blood stream infections [55,56]. Previously, T2SS has been shown to be strongly involved in P. aeruginosa chronic infection [57].…”
Section: Discussionmentioning
confidence: 99%